2016
DOI: 10.1007/s00268-016-3846-x
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Resection with Major Blood Vessel Reconstruction for Locally Invasive Retroperitoneal Paragangliomas: A 15‐Year Experience with Literature Review

Abstract: En bloc resection with major blood vessel reconstruction can be successfully performed and provide satisfactory outcomes for patients with locally invasive retroperitoneal PGs. This technique may become a standard surgical strategy for properly selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Homsy et al [10] in a recent study, described seven aortic resections in seventh casuist patients with abdominal sarcoma major vessel evolvement. They concluded that oncovascular surgery enables radical resection required for reasonable local control of retroperitoneal sarcomas and is associat-ed with an acceptable level of complications peri-operatively and during follow-up [13]. We believe this conclusion can be transposed to pediatric patients.…”
Section: Discussionmentioning
confidence: 74%
“…Homsy et al [10] in a recent study, described seven aortic resections in seventh casuist patients with abdominal sarcoma major vessel evolvement. They concluded that oncovascular surgery enables radical resection required for reasonable local control of retroperitoneal sarcomas and is associat-ed with an acceptable level of complications peri-operatively and during follow-up [13]. We believe this conclusion can be transposed to pediatric patients.…”
Section: Discussionmentioning
confidence: 74%
“…For more common tumours like WT and HBL, protocols are available and they dictate neoadjuvant NACT 24,30 . On the contrary, Paragangliomas have typically a poor response to NACT and therefore primary en-bloc resection of mass and vessels must be considered 31,32,33,21 After resection of the involved vessel, a decision needs to be made regards simple ligation, or reconstruction. 34 This will depend on whether an artery or vein is involved, and what it supplies: most arteries and the portal vein will require reconstruction, whilst the IVC can be ligated with impunity.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltration is a rare cause of aortic rupture. Besides the germ cell testicular cancer [ 16 ], abdominal aortic invasion has also been reported in other types of malignancies as soft tissue sarcomas [ 17 20 ], paragangliomas [ 21 ], lymphomas [ 22 ] and gynecological tumors [ 23 ]. Most authors consent that endovascular aortic intervention is an effective and safe method which should be encouraged to provide a definite therapeutic impact in a subset of patients who would otherwise not be candidates for curative surgery.…”
Section: Discussionmentioning
confidence: 99%